Iusnaturalismo y derechos humanos - Antonio E. Pérez Luño (Araucaria)
This study considers object contribute the defense of the good reasons of the Natural Law Theory on human rights. For this, the arguments are exposed that they justify the focus Natural Law Theory of their study. It to such end are analyzed the clarification of the concept and foundation of the human rights from the perspective Natural Law Theory; the full historical conscience from which the critical current of the Natural Law Theory assumes the analysis of the freedoms; and, in definitive, the implications and contributions that the conception of the Natural Law Theory on human rights had in the philosophical, juridical and political plane